CAD-BASED 3D PRINTING EDUCATION TO ENHANCE THE COMPETENCE OF VOCATIONAL STUDENTS OF SMK BABAT LAMONGAN - Juniani, Anda Iviana; Wibisono, Fipka; Kurniawan, Bayu W.; Indrawan, Rizal; Hamzah, Fais; Sidi, Pranowo; Purnomo, Dhika A.; Rachman, Farizi; Ardliana, Thina (Sawala : Jurnal pengabdian Masyarakat Pembangunan Sosial, Desa dan Masyarakat, 2024)
Printing in three dimensions is becoming increasingly vital for vocational students. Incorporating 3D printing into vocational training courses and educational programs provides students with numerous benefits and prepares them for technical professions in various industries. This article aims to develop 3D printing training that is CAD-based for SMK Babat Lamongan. Students can experience real-world models of complex mathematical equations, graphs, and arrangements through 3D printing. It enables students with difficulty visualizing these concepts to comprehend them more readily. By learning 3D printing now, vocational students are preparing for the changing job market and global economy of the twenty-first century. This article shows that skills in 3D printing are precious for vocational students. They provide students with hands-on experience, foster creativity, and prepare them for technical vocations. Incorporating 3D printing into vocational education programs can give students the necessary skills for the future workforce.